Botrytis cinerea G Protein β Subunit Bcgb1 Controls Growth, Development and Virulence by Regulating cAMP Signaling and MAPK Signaling - Jiejing Tang (Journal of Fungi, 2021)
Botrytis cinerea is a necrotrophic phytopathogenic fungus that causes gray mold disease in many crops. To better understand the role of G protein signaling in the development and virulence of this fungus, the G protein β subunit gene Bcgb1 was knocked out in this study. The ΔBcgb1 mutants showed reduced mycelial growth rate, but increased aerial hyphae and mycelial biomass, lack of conidiation, failed to form sclerotia, increased resistance to cell wall and oxidative stresses, delayed formation of infection cushions, and decreased virulence. Deletion of Bcgb1 resulted in a significant reduction in the expression of several genes involved in cAMP signaling, and caused a notable increase in intracellular cAMP levels, suggesting that G protein β subunit Bcgb1 plays an important role in cAMP signaling. Furthermore, phosphorylation levels of MAP kinases (Bmp1 and Bmp3) were increased in the ΔBcgb1 mutants. Yeast two-hybrid assays showed that Bcgb1 interacts with MAPK (Bmp1 and Bmp3) cascade proteins (BcSte11, BcBck1, BcMkk1, and BcSte50), and the Bmp1-regulated gene Bcgas2 was up-regulated in the ΔBcgb1 mutant. These results indicated that Gβ protein Bcgb1 is involved in the MAPK signaling pathway in B. cinerea. In summary, our results revealed that Gβ protein Bcgb1 controls development and virulence through both the cAMP and MAPK (Bmp1 and Bmp3) signaling pathways in B. cinerea.